Pemodelan Perilaku Kelarutan Molekul Air terhadap Variasi Pelarut pada Permukaan CulnS2/ZnS Quantum Dots Menggunakan Pendekatan ab-initio berbasis Density Functional Theory - Permadi, Adi (Institut Teknologi Adhi Tama Surabaya, 2024)
This study investigates the solubility behavior of water molecules on the surface of CuInS₂/ZnS Quantum Dots (QDs) in different solvents using an Ab Initio approach based on Density Functional Theory (DFT). The research evaluates the influence of solvent dielectric constant on surface potential energy and solute-solvent interaction energy. The study reveals that hydrogen bonding, dipole-dipole interactions, and van der Waals forces significantly affect QDs stability and size. The findings indicate that solvents with higher dielectric constants destabilize nanoparticles, leading to electron transfer between particles. Among the tested solvents, chloroform provides an optimal balance between solubility, stability, and band gap ( 1.68 eV). These results contribute to a deeper understanding of solvent-mediated effects on QDs, essential for their application in optoelectronics and bio-imaging.